Prices vs. Quantities: A Critical Note on the Use of Approximations - Malcomson, J. M. (Review of Economic Studies, 1978)
Journal Article Prices vs. Quantities: A Critical Note on the Use of Approximations Get access James M. Malcomson James M. Malcomson University of York Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 1, February 1978, Pages 203–207, https://doi.org/10.2307/2297096 Published: 01 February 1978